PENYULUHAN NAPZA PADA SISWA SMP NEGERI 02 MAYANG SEBAGAI UPAYA PENCEGAHAN PENYALAHGUNAAN OBAT TERLARANG - Wahidah, Nur; Jannah, Nur; Afandi, Moch. Yusuf Sholeh; nafi’ah, Jamilatun (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
Drug abuse is a serious problem that threatens the younger generation. Early prevention efforts are very important, especially among teenagers. This community service activity aims to evaluate the effectiveness of the drug education program implemented at SMP Negeri 02 Mayang. This counseling involved 160 class IX students and was carried out in two sessions. The education material includes the definition of drugs, types of drugs, the dangers of abuse, and prevention efforts. The methods used are lectures, discussions and questions and answers. To measure the effectiveness of the program, a pre-test and post-test were carried out. The results of this outreach activity show a significant increase in students' knowledge about drugs. This indicates that the outreach program carried out is effective in increasing students' awareness of the dangers of drug abuse. Apart from that, students' enthusiasm in participating in activities shows that they have an interest in learning more about the dangers of drugs. However, further research is still needed to measure the long-term impact of this program on student behavior. Apart from that, more intensive efforts need to be made to involve all components of society in preventing drug abuse.